Trafficking and regulation of the serotonin transporter - Magnani, Francesca (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2004)
The serotonin transporter (SERT) is responsible for the clearance of serotonin from the synaptic cleft. Together with the norepinephrine transporter and dopamine transporter, SERT is of great interest because it is the molecular target for many antidepressants, and substances of abuse, such as cocaine and MDMA (Ecstasy). Although the involvement of SERT in serotonin clearance has been clearly established for many years, our understanding of how the serotonin transporter is regulated in vivo is still fragmentary. The aim of my PhD project was to investigate the association of SERT with proteins and/or lipids that may regulate the trafficking and function of the serotonin transporter.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin